2011
DOI: 10.2486/indhealth.ms1201
|View full text |Cite
|
Sign up to set email alerts
|

Subjective Symptoms of Female Workers Sorting Goods in Summer

Abstract: Subjective musculoskeletal symptoms are more frequently complained about in cold store work and in related conditions than those experienced in normal temperature work. This cross sectional study was undertaken to evaluate the effects of indoor cooling and cold storage goods on the prevalence of subjective symptoms in summer. Female workers sorting cold storage goods (exposed group) were the main subjects of this study (n=47). We also included a group of female workers engaged sorting dry goods as the unexpose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(36 citation statements)
references
References 15 publications
(26 reference statements)
0
36
0
Order By: Relevance
“…A previous Thai study [12] compared cold storage and office workers in the frozen food industry and found a higher prevalence of respiratory symptoms among the cold storage workers but did not investigate performance degradation, thirst, and drying of the mouth. We are not aware of other studies comparing the latter symptoms between job categories, although the high prevalence of musculoskeletal, circulatory, and respiratory symptoms among cold workplace workers has been well documented [4,8,9,27,45]. While thirst and drying of the mouth suggest insufficient fluid intake and dehydration, they have not been previously described among cold workplace workers.…”
Section: Prevalence Of Symptoms According To Personal and Workrelatedmentioning
confidence: 84%
“…A previous Thai study [12] compared cold storage and office workers in the frozen food industry and found a higher prevalence of respiratory symptoms among the cold storage workers but did not investigate performance degradation, thirst, and drying of the mouth. We are not aware of other studies comparing the latter symptoms between job categories, although the high prevalence of musculoskeletal, circulatory, and respiratory symptoms among cold workplace workers has been well documented [4,8,9,27,45]. While thirst and drying of the mouth suggest insufficient fluid intake and dehydration, they have not been previously described among cold workplace workers.…”
Section: Prevalence Of Symptoms According To Personal and Workrelatedmentioning
confidence: 84%
“…Overall, 37 articles reporting on 36 unique studies were deemed eligible and selected. 34-70 Some articles appeared to be relevant upon initial review, but were excluded because the independent effects of the nine healthy buildings determinants could not be concluded. 71-78
Figure 1.PRISMA flow diagram of search results.
…”
Section: Resultsmentioning
confidence: 99%
“…Back pain was addressed in 26 articles, 34,35,38-44,47,50,51,53-57,59-61,64,66-70 and neck pain was addressed in 22 articles. 36-38,40-46,48,49,52,53,56-58,61-63,65,68 The healthy building determinants addressed were: air quality (ventilation) (N = 10), 37,38,40,43,46,55,60,65,66,69 dust and pests (N = 2), 54,60 lighting and views (N = 10), 35,36,43,46-…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, two-wheeler users are more prone for musculoskeletal pain and higher level of cumulative trauma. As the two groups were well matched, the factor we felt responsible for such a difference in pain scores is lack of chance to change posture during commute, lack of back support, recurrent active recruitment of muscles for balancing purpose and to handle the weight of the bike, and environmental stress factors, such as exposure to cold 8,9 or heat. 10 Our subjects were from an urban environment and riding in traffic conditions may be more stressful as compared with a rural or suburban environment.…”
Section: Prevalence Of Painmentioning
confidence: 99%